PEMBERDAYAAN EKONOMI WANITA MELALUI PENGEMBANGAN BATIK ECOPRINT: INOVASI KREATIF DAN RAMAH LINGKUNGAN DI LIMO, DEPOK - Nastiti, Heni; Pangestuti, Dewi Cahyani; Miftah, Munasiron; Sumilir, Sumilir (LPPM Universitas Bina Bangsa, 2024)
The problem faced by women in Limo, Depok is limited access to economic opportunities and specific skills for business development. This program aims to empower women through training and mentoring in ecoprint batik techniques, enabling them to establish self-sustaining, environmentally friendly creative businesses. The methodology includes outreach, intensive training, business management mentoring, and evaluation of results. Conducted over three sessions in June 2024, participants were taught technical Ecoprint skills and received business management guidance. Results show significant improvements in technical skills and business understanding, increasing participants' confidence in running independent businesses. The program has had a positive impact on the local economy and empowered participants for the long term. It is recommended that the program be expanded to include advanced training and broader collaboration to support the sustainability of participants' businesses